2017
DOI: 10.1016/j.actamat.2017.01.058
|View full text |Cite
|
Sign up to set email alerts
|

On the crystallographic characteristics of nanobainitic steel

Abstract: This study aims to elucidate the crystallographic characteristics of bainite transformed in a temperature range of 200-350°C, where a nanobainitic structure is formed. The microstructure, consisting of bainitic ferrite laths and retained austenite, became significantly refined and its crystallographic arrangement changed with a decrease in the phase transformation temperature. At 200-250°C, the bainite packets mostly consisted of one or more blocks (i.e. bainitic ferrite laths and retained austenite lamellae) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 55 publications
(75 reference statements)
6
17
0
Order By: Relevance
“…It is probable that this effect is a consequence of the change of the transformation temperature. This confirms Beladi's idea that the phase transformation temperature has a significant effect on the OR between the parent phase and the daughter phase [6]. The OR of LM was mainly K-S OR, since the specimen in our study was composed of low-carbon high alloy.…”
Section: Determination Of Orientation Relationshipssupporting
confidence: 90%
See 2 more Smart Citations
“…It is probable that this effect is a consequence of the change of the transformation temperature. This confirms Beladi's idea that the phase transformation temperature has a significant effect on the OR between the parent phase and the daughter phase [6]. The OR of LM was mainly K-S OR, since the specimen in our study was composed of low-carbon high alloy.…”
Section: Determination Of Orientation Relationshipssupporting
confidence: 90%
“…Abundant work has been conducted to introduce some crystallographic terminologies considering γ to α phase transformation in carbon steels. Table 1 presents various possible orientation relationships (ORs) between the γ parent phase and the α daughter phase [6], that is, Kurdjumov-Sachs (K-S) OR, Nishiyama-Wassermann (N-W) OR, Greninger-Troiano (G-T) OR, and Pitsch OR. In the manuscript, we will only consider the crystallographic orientation variants from a certain prior austenite crystal that are based on K-S ORs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that misorientation angles mainly distributed between 42° and 47° within the isothermal temperature range, typically shown in Figure a. It was reported that the ideal misorientation angles for K‐S and N‐W OR between ferrite and austenite were 43° and 46°, respectively . Thus, in the present work, misorientation angles at 43° ± 1° and 46° ± 1° were determined as the ones corresponded to type K‐S boundary and type N‐W boundary, respectively.…”
Section: Resultssupporting
confidence: 56%
“…In all of these applications, there is potential for improved performance by enhancing the surface properties. There have been studies of microstructure and property relationships [1][2][3][4], crystallography [5,6], wear behavior [7,8], and thermal tempering [9,10] of nano-bainitic steels (henceforth termed low temperature bainite) but it has been no attempt to enhance its surface properties.…”
Section: Introductionmentioning
confidence: 99%